Preparados orgánicos (Croton lechleri y Propolis de Apis mellifera) en el tratamiento de mastitis clínica y subclínica en bovinos de leche - Vera Cedeño, Cristóbal Colón (2020)
The objective of the research was to evaluate the effectiveness of organic biopreparations as a treatment of clinical and subclinical mastitis in cattle in production. Fifteen cows were selected, grouped into three groups of five animals each for the application (for three days) of the respective treatments: Drago Blood (Croton lechleri) 5%, Propolis (Apis mellífera Propolis) 5% and Cephalexin (commercial). In addition, the California Mastitis Test (CMT) and milk samples were taken, at the level of each nipple, to perform the Somatic Cell Number (NCS), before the application of the treatments and 48 hours after it was completed the application of the preparations. A DCA with subsamples was used, for three treatments with five repetitions, for a total of 60 observations. The variables measured were: Number of somatic cells (NCS / ml), Amount of agglutination of milk subsamples (CMT) and effectiveness of organic biopreparations and Cephalexin. The results infer a non-significant effect (p˃0.05) in the treatments for the variables studied. It was observed in the values obtained a better behavior among the organic products in comparison to the commercial one; highlighting the Propolis (Apis mellífera Propolis) 5% that reduced NCS and agglutination of milk, which presented the lowest cost at the economic level. It is concluded that the application of organic products (Propolis and Drago Blood) maintains a similarity in efficacy with respect to the commercial product (Cephalexin).